Nghiên cứu chế tạo vật liệu compozit bằng phương pháp chuyển nhựa vào khuôn có hỗ trợ chân không - Tùng, Nguyễn Huy; Duy Linh, Nguyễn Phạm; Hiệp, Nguyễn Văn; Hưng, Nguyễn Thị; Sơn, Vũ Văn (Vietnam Journal of Chemistry, 2016)
The parameter of VARTM process such as flowing time, permeability was investigated. The experimental results so that when increasing number of layer of glass fiber, the flow time of resin in the VARTM mould decrease because of porousity of glass fiber. The permeability of woven glass fiber is better than that of mat fiber. The mechanical properties of composite materials were investigated. The increasing of glass fiber content will rise tensile and bending strength of the materials. The best strength was obtained at the 65 % fiber content.